Thermoplastic resin composition, method for producing the same, and molded article containing the same

JP2026534420APending Publication Date: 2026-10-16LG CHEM LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025523615
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-05
Filing Date
2024-07-26
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0036】 本発明に係る熱可塑性樹脂組成物は、市場のレーダー性能の改善及びレドームの適用用途の多角化のニーズに応じて、トレードオフ(trade off)の関係にある熱変形温度と衝撃強度を改善することで、より多様なレドームをはじめとする電装部品に使用可能な熱可塑性樹脂を提供する効果がある。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026534420000001_ABST
    Figure 2026534420000001_ABST
Patent Text Reader

Abstract

The present invention relates to a thermoplastic resin composition, a method for producing the same, and a molded article containing the same. The thermoplastic resin composition according to the present invention has the effect of being usable in a wider variety of electrical components, including radomes, by improving the heat distortion temperature and impact strength, which are in a trade-off relationship, through a change in the material used, thereby satisfying the heat resistance required in line with the improvement of radar performance and the impact strength required in line with the diversification of radome applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] 〔Cross-Reference to Related Applications〕 This application claims the benefit of priority based on Korean Patent Application No. 10-2023-0132213 filed on October 05, 2023, and all contents disclosed in the documents of the said Korean patent application are incorporated as part of the present specification.

[0002] The present invention relates to a thermoplastic resin composition, a method for producing the same, and a molded article comprising the same. More specifically, the present invention relates to a thermoplastic resin composition that can be used in various electrical components including a wider variety of radomes by improving the heat deflection temperature and impact strength that are in a trade-off relationship, a method for producing the same, and a molded article comprising the same.

Background Art

[0003] Polyester resins are applied to various components including automotive interior materials due to their low unit price, mechanical physical properties, thermal characteristics, and excellent moldability.

[0004] In particular, polybutylene terephthalate (PBT) has a low crystallinity and thus is used as a laser-transmitting material. At this time, polycarbonate (PC), which is an amorphous resin, is mixed and used as a material for improving laser transmittance.

[0005] However, when an amorphous resin is mixed with a polyester resin having low crystallinity, a problem arises in that the heat deflection temperature and impact strength are reduced.

[0006] Accordingly, there is an actual need to develop a material that improves heat resistance and impact strength and can be used in various electrical components including a wider variety of radomes.

Prior Art Documents

Patent Documents

[0007]

Patent Document 1

[0008] To address the problems of the conventional technology described above, the present invention aims to provide a thermoplastic resin composition that is economically superior and can be used in a wider variety of electrical components, including radomes, by improving heat resistance and impact strength in response to the market's needs for improved radar performance and diversification of radome applications.

[0009] Another object of the present invention is to provide a method for producing the thermoplastic resin composition.

[0010] Furthermore, the present invention aims to provide a molded article using the thermoplastic resin composition described above.

[0011] The above-mentioned and other objectives of the present invention can all be achieved by the present invention as described below. [Means for solving the problem]

[0012] To achieve the above objective, the present invention comprises I) polybutylene terephthalate (PBT), polycarbonate (PC), and siloxane-based copolycarbonate (Si-PC); and glass fiber; wherein the weight ratio of polycarbonate (PC) to siloxane-based copolycarbonate (Si-PC) to polybutylene terephthalate (PBT) is in the range of 4:6 to 6:4 (PBT:PC + Si-PC), and the weight ratio of polycarbonate (PC) to siloxane-based copolycarbonate (Si-PC) satisfies 3.5:6.5 to 6.5:3.5 (PC:Si-PC). When the amount of polybutylene terephthalate (PBT) used is a, the amount of glass fiber used is b, and the amount of polycarbonate (PC) used is c, then a > b > c is satisfied. The present invention provides a thermoplastic resin composition characterized in that, when the amount of polybutylene terephthalate (PBT) used is a', the amount of glass fiber used is b', and the amount of siloxane-based copolycarbonate (Si-PC) used is d, the condition a' > b' > d is met.

[0013] II) In I) above, the polybutylene terephthalate (PBT) may be present in an amount of 31.3 to 37% by weight of 100% of the total amount of all components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based copolycarbonate (Si-PC), glass fiber, and additives).

[0014] III) In I) or II) above, the glass fibers may be present in an amount of 10 to 40% by weight of the total amount of all components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based copolycarbonate (Si-PC), glass fibers, and additives) per 100% by weight.

[0015] IV) In the above I) to III), the siloxane-based copolycarbonate (Si-PC) may be included in an amount of 22% by weight or less of the total amount of all components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based copolycarbonate (Si-PC), glass fiber, and additives) per 100% by weight.

[0016] Furthermore, the present invention provides a thermoplastic resin composition characterized in that, in a total of 100% by weight of V) polybutylene terephthalate (PBT), polycarbonate (PC), and siloxane-based copolycarbonate (Si-PC); glass fibers; and additives, the composition contains 31.3 to 37% by weight of the polybutylene terephthalate (PBT), 24% by weight or less of the polycarbonate (PC), 24% by weight or less of the siloxane-based copolycarbonate (Si-PC), and 10 to 40% by weight of the glass fibers.

[0017] VI) In the above V), the polybutylene terephthalate (PBT) may have a weight average molecular weight of 10,000 to 80,000 g / mol.

[0018] VII) In the above V) to VI), the polybutylene terephthalate (PBT) and the polycarbonate (PC) may be contained at a weight ratio (PBT:PC) of 1:0.3 to 1:1.1.

[0019] VIII) In the above V) to VII), the polycarbonate (PC) may be contained in an amount of 13 to 21 wt% based on 100 wt% of the total of polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based copolycarbonate (Si-PC), glass fiber and additives.

[0020] IX) In the above V) to VIII), the siloxane-based copolycarbonate (Si-PC) may be contained in an amount of 13 to 21 wt% based on 100 wt% of the total of polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based copolycarbonate (Si-PC), glass fiber and additives.

[0021] X) In the above V) to IX), the polycarbonate (PC) may have a melt index of 0.1 to 30 g / 10min measured at 300°C under 1.2 kg in accordance with ASTM D1238.

[0022] XI) In the above V) to X), the polycarbonate (PC) may have a mold shrinkage of 0.005 to 0.007 in / in measured in accordance with ASTM D955.

[0023] XII) In the above V) to XI), the glass fiber may be a chopped strand having an average diameter of 7 to 15 μm and an average length of 3 to 9 mm.

[0024] XIII) In the above V) to XII), the additive may comprise one or more selected from a nucleating agent, a lubricant, talc, an antioxidant and a colorant.

[0025] XIV) In any one of the above V) to XIII), the thermoplastic resin composition may be a material used for electrical component parts.

[0026] XV) In any one of the above V) to XIV), the thermoplastic resin composition may have a laser transmittance (%) of 67.5% or higher, as measured using ETM-31 equipment (980 nm) from EVlaser.

[0027] XVI) In any one of the above V) to XV), the thermoplastic resin composition may have a heat deflection temperature of 167.6°C or higher, as measured under a load of 0.45 MPa (flatwise) on a test specimen with a thickness of 4 mm in accordance with ISO 75.

[0028] XVII) In any one of the above V) to XVI), the thermoplastic resin composition may have a room temperature Izod impact strength (23°C, Notched) of 9.5 kJ / m, as measured on a test specimen with a thickness of 4 mm in accordance with ISO 180 2 or higher.

[0029] XVIII) In any one of the above I) to XVII), the thermoplastic resin composition may have a low temperature Izod impact strength (-30°C, Notched) of 8.4 kJ / m, as measured on a test specimen with a thickness of 4 mm in accordance with ISO 180 2 or higher.

[0030] The present invention further provides XIX) a method comprising the step of feeding polybutylene terephthalate (PBT), polycarbonate (PC) and siloxane-based copolycarbonate (Si-PC); glass fibers; and additives into an extruder, and performing melt-kneading and extrusion, wherein the weight ratio of polycarbonate (PC) plus siloxane-based copolycarbonate (Si-PC) to the polybutylene terephthalate (PBT) is within the range of 4:6 to 6:4 (PBT:PC+Si-PC), and the weight ratio of the polycarbonate (PC) to the siloxane-based copolycarbonate (Si-PC) satisfies 3.5:6.5 to 6.5:3.5 (PC:Si-PC), When the amount of polybutylene terephthalate (PBT) used is a, the amount of glass fiber used is b, and the amount of polycarbonate (PC) used is c, then a > b > c is satisfied. The present invention provides a method for producing a thermoplastic resin composition, characterized in that when the amount of polybutylene terephthalate (PBT) used is a', the amount of glass fiber used is b', and the amount of siloxane-based copolycarbonate (Si-PC) used is d, the condition a' > b' > d is satisfied.

[0031] Furthermore, the present invention provides a method for producing a thermoplastic resin composition, characterized by comprising the steps of putting the following into an extruder: melt-kneading and extrusion, in a total of 100% by weight of XX) polybutylene terephthalate (PBT), polycarbonate (PC), and siloxane-based copolycarbonate (Si-PC); glass fibers; and additives, the polybutylene terephthalate (PBT) being present in an amount of 31.3 to 37% by weight, the polycarbonate (PC) being present in an amount of 24% by weight or less, the siloxane-based copolycarbonate (Si-PC) being present in an amount of 24% by weight or less, and the glass fibers being present in an amount of 10 to 40% by weight.

[0032] Furthermore, the present invention provides a molded article characterized by containing the thermoplastic resin composition described above (XXI).

[0033] XXII) In XXI) above, the molded product may be an electrical component.

[0034] XXIII) In XXI) or XXII) above, the electrical component may be a connector, a sensor component, or a component for a parking brake system, etc.

[0035] XXIV) In XXI) or XXIII) above, the sensor component may be a radome, an advanced driver-assistance system (ADAS), or the like. [Effects of the Invention]

[0036] The thermoplastic resin composition according to the present invention has the effect of providing a thermoplastic resin that can be used in a wider variety of electrical components, including radomes, by improving the heat distortion temperature and impact strength, which are in a trade-off relationship, in response to the market's needs for improved radar performance and diversification of radome applications.

[0037] Therefore, the thermoplastic resin composition according to the present invention is applicable to various fields of electrical components, including connectors, sensors, and parking brake systems, which require specific physical properties. [Brief explanation of the drawing]

[0038] [Figure 1] This is a photograph of a test piece in which a material according to one embodiment of the present invention was injection-molded, and the laser transmittance was measured at one location and another location. [Figure 2] This figure shows a cross-section of an extruder used in a method for manufacturing a molded product according to one embodiment of the present invention. [Best Mode for Carrying Out the Invention]

[0039] The present invention will be described in more detail below to aid in understanding the invention.

[0040] The terms and words used herein and in the claims shall not be construed to be limited to their ordinary or dictionary meanings, but rather to be construed in a sense and concept consistent with the technical idea of ​​the present invention, taking into account that inventors can appropriately define the concepts of terms in order to best describe their invention.

[0041] In this document, unless otherwise defined, the meaning of "containing" can be defined as "polymerized and manufactured containing," "polymerized containing," or "containing as a unit of origin."

[0042] Unless otherwise specified, all numbers, values, and / or expressions used in this description to describe the quantities of components, reaction conditions, polymer compositions, and formulations should be understood to be modified in all cases by the term “approximately,” as such numbers are approximations that reflect the various uncertainties of measurement that arise in obtaining such values ​​among others. Furthermore, where numerical ranges are disclosed in this description, such ranges are continuous and, unless otherwise noted, include all values ​​from the minimum to the maximum within such range. Additionally, where such ranges refer to integers, they include all integers from the minimum to the maximum, unless otherwise specified.

[0043] In this description, when a range is given for a variable, the variable is understood to include all values ​​within the given range, including the given endpoint of the range. For example, the range "5-10" is understood to include not only the values ​​5, 6, 7, 8, 9, and 10, but also any subranges such as 6-10, 7-10, 6-9, 7-9, and any values ​​between integers that are within the given range, such as 5.5-8.5 and 6.5-9. Similarly, the range 10-30% is understood to include not only all integers up to 30%, such as 10%, 11%, 12%, and 13%, but also any values ​​between rational numbers within the given range, such as 10.5%, 15.5%, and 25.5%.

[0044] The inventors of this invention have confirmed that when polycarbonate (PC) is mixed with siloxane-based copolycarbonate (Si-PC), the heat distortion temperature and impact strength of the molded product are improved, and that the heat resistance, which is important for radar performance, and the impact strength, which is important for diversifying the applications of radomes, are greatly improved. They further pursued research and completed the present invention.

[0045] A thermoplastic resin composition according to one embodiment of the present invention includes, as an example, polybutylene terephthalate (PBT), polycarbonate (PC), and siloxane-based copolycarbonate (Si-PC); and glass fibers.

[0046] According to one embodiment of the present invention, the content ratio of polybutylene terephthalate (PBT) to polycarbonate (PC) and siloxane-based copolycarbonate (Si-PC) may, for example, be within the range of a weight ratio of 4:6 to 6:4 (PBT:PC + Si-PC).

[0047] Within the range of the aforementioned weight ratio (PBT:PC+Si-PC), a balance of physical properties between laser transmittance, thermal distortion temperature, and impact strength can be provided. Preferably, the weight ratio (PBT:PC+Si-PC) may be 4.5:5.5 to 6:4, and more preferably, it may be 4.5:5.5 to 5.5:6.5.

[0048] The components constituting the thermoplastic resin composition will be described in detail below.

[0049] Polybutylene terephthalate (PBT) Polybutylene terephthalate (PBT) according to one embodiment of the present invention imparts moldability and chemical resistance to thermoplastic resin compositions containing it.

[0050] The aforementioned polybutylene terephthalate (PBT) prevents the penetration of chemicals from entering from the outside, while also improving the flowability of the thermoplastic resin composition containing it during injection molding, thereby improving the appearance quality.

[0051] The aforementioned polybutylene terephthalate (PBT) with an intrinsic viscosity (IV) of 0.6 to 1.4, or 0.7 to 1.2, is suitable for improving the trade-off relationship between thermal distortion temperature and impact strength.

[0052] Unless otherwise specified, the intrinsic viscosity is the value obtained by completely dissolving the sample to be measured in methylene chloride solvent at a concentration of 0.05 g / ml, filtering the filtrate using a filter, and measuring it at 20°C using an Ubbelohde viscometer.

[0053] The polybutylene terephthalate (PBT) may, for example, have a weight-average molecular weight (Mw) of 10,000 to 80,000 g / mol, specifically 20,000 to 100,000 g / mol, and preferably 30,000 to 90,000 g / mol. More preferably, it may be 40,000 to 80,000 g / mol, or 50,000 to 70,000 g / mol.

[0054] In this description, the weight-average molecular weight (Mw) can be measured by end-group analysis or gel permeation chromatography (GPC).

[0055] As a specific example, the weight-average molecular weight using the aforementioned GPC can be measured using tetrahydrofuran as the eluent, and the measurement can be performed through GPC (Gel Permeation Chromatography, waters breeze) as a relative value to a standard PS (standard polystyrene) sample.

[0056] The polybutylene terephthalate (PBT) may be manufactured and used by methods known in the art, or a commercially available substance may be used, and is not particularly limited.

[0057] The polybutylene terephthalate (PBT) may be included in an amount of 31.3 to 37% by weight, specifically 32 to 36% by weight, and preferably 33 to 36% by weight, in 100% by weight of the total amount of all components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based copolycarbonate (Si-PC), glass fiber, and additives), in an example of 31.3 to 37% by weight, more specifically 32 to 36% by weight, in this case, a balance of physical properties between the heat distortion temperature and impact strength can be achieved.

[0058] Polycarbonate (PC) The aforementioned polycarbonate (PC) may, for example, have a melt index of 0.1 to 30 g / 10 min, preferably 1 to 25 g / 10 min, and more preferably 10 to 22 g / 10 min, as measured at 300°C and 1.2 kg in accordance with ASTM D1238. Within this range, there is an effect of improving the thermal properties such as moldability and processability, as well as the workability, of the final thermoplastic resin composition.

[0059] If the melting index exceeds 30g / 10min, it may result in uneven quality and molding defects.

[0060] The polycarbonate (PC) may, for example, be a solid-phase polymer of an aromatic dicarboxylic acid or its derivative, an aliphatic diol, or a polyalkylene oxide.

[0061] The aromatic dicarboxylic acid or its derivative and the aliphatic diol can constitute the hard fraction of the polycarbonate (PC) described above, and the polyalkylene oxide can constitute the soft fraction of the polycarbonate (PC) described above.

[0062] The aromatic dicarboxylic acid may be one or more selected from the group consisting of, for example, terephthalic acid (TPA), isophthalic acid (IPA), 2,6-naphthalene dicarboxylic acid (2,6-NDCA), 1,5-naphthalene dicarboxylic acid (1,5-NDCA), 1,4-cyclohexane dicarboxylic acid (1,4-CHDA), dimethyl terephthalate (DMT), dimethyl isophthalate (DMI), 2,6-dimethyl naphthalene dicarboxylate (2,6-NDC), and dimethyl 1,4-cyclohexane dicarboxylate (DMCD), and preferably dimethyl terephthalate (DMT).

[0063] The aromatic dicarboxylic acid or its derivative may, for example, be present in an amount of 25 to 60% by weight, preferably 29 to 55% by weight, and more preferably 34 to 45% by weight, of 100% by weight of the total amount of all components constituting the polycarbonate (PC) (aromatic dicarboxylic acid or its derivative, aliphatic diol, and polyalkylene oxide), and within this range, there is an effect of excellent reaction balance.

[0064] The aliphatic diol may, for example, be a diol with a number-average molecular weight (Mn) of 300 g / mol or less. Specifically, it may be one or more selected from the group consisting of ethylene glycol, propylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,4-cyclohexanedimethanol, and preferably 1,4-butanediol.

[0065] In this description, the number-average molecular weight (Mn) can be measured by end-group analysis or gel permeation chromatography (GPC).

[0066] As a specific example, the number-average molecular weight using the aforementioned GPC can be measured using tetrahydrofuran as the eluent, and the measurement can be performed through GPC (Gel Permeation Chromatography, waters breeze) as a relative value to a standard PS (standard polystyrene) sample.

[0067] As an example, the aliphatic diol may be present in an amount of 10 to 40% by weight, preferably 15 to 40% by weight, and more preferably 20 to 30% by weight, of the total amount of all components constituting the polycarbonate (PC) (aromatic dicarboxylic acid or its derivative, aliphatic diol, and polyalkylene oxide), and within this range, there is an effect of excellent reaction balance.

[0068] The polyalkylene oxide can constitute a soft fraction containing an aliphatic component whose number-average molecular weight (Mn) is, for example, 600-3,000 g / mol, 1,000-2,500 g / mol, 1,500-2,200 g / mol, or 2,000-3,000 g / mol.

[0069] The polyalkylene oxide may be, for example, one or more selected from the group consisting of polyoxyethylene glycol, polypropylene glycol, poly(tetramethylene ether) glycol (PTMEG), polyoxyhexamethylene glycol, copolymers of ethylene oxide and propylene oxide, ethylene oxide addition polymers of polypropylene oxide glycol, and copolymers of ethylene oxide and tetrahydrofuran, and is preferably poly(tetramethylene ether) glycol (PTMEG).

[0070] For example, a polyalkylene oxide with a number-average molecular weight (Mn) of 600 to 3,000 g / mol may also be poly(tetramethylene ether) glycol.

[0071] As another example, a polyalkylene oxide with a number-average molecular weight (Mn) of 2,000 to 3,000 g / mol may be polypropylene glycol with ethylene oxide capping at the ends.

[0072] As an example, the polyalkylene oxide may be present in an amount of 15 to 60% by weight, preferably 15 to 55% by weight, and more preferably 15 to 45% by weight, of the total amount of all components constituting the polycarbonate (PC) (aromatic dicarboxylic acids or their derivatives, aliphatic diols, and polyalkylene oxides) per 100% by weight, and within this range, there is an effect of excellent reaction balance.

[0073] The polycarbonate (PC) may contain additives as needed; for example, branching agents can be used to increase the melt viscosity and melt tension of the elastomer.

[0074] The branching agent may be, for example, one or more selected from the group consisting of glycerol, pentaerythritol, trimellitic acid or its anhydride, trimethylolpropane, and neopentyl glycol, and preferably trimellitic acid anhydride.

[0075] The branching agent may be included, for example, in an amount of 0.05 to 0.1 parts by weight, preferably 0.05 to 0.09 parts by weight, and more preferably 0.06 to 0.09 parts by weight, per 100 parts by weight of the total amount of all components constituting the polycarbonate (PC) (aromatic dicarboxylic acid or its derivative, aliphatic diol, and polyalkylene oxide). Within this range, the intrinsic viscosity can be easily adjusted during melt polymerization by increasing the melt viscosity.

[0076] The polycarbonate (PC) may be a solid-phase polymer of the melt (shrink) polymer of the aforementioned components.

[0077] As a specific example, the aforementioned polycarbonate (PC) can be produced by transesterifying the aforementioned aromatic dicarboxylic acid, aliphatic diol, and polyalkylene oxide under a titanium butoxide (TBT) catalyst at 140-215°C for approximately 120 minutes to produce a bis(4-hydroxy)butyl terephthalate (BHBT) oligomer, then adding an additional TBT catalyst and carrying out a melt (condensation) polymerization reaction at 215-245°C for approximately 120 minutes while gradually reducing the pressure from 760 torr to 0.3 torr.

[0078] The aforementioned melt (shrink) polymerization reaction can be carried out, for example, until the melt (shrink) polymer has a melt flow index (MFI) measured at 230°C and a load of 2.16 kg in accordance with ASTM D1238, within the range of 20 to 25 g / 10 min.

[0079] After the melt (condensation) polymerization reaction is completed, the strand can be pelletized by discharging it while maintaining nitrogen pressure inside the reactor.

[0080] The aforementioned pellets can, for example, be subjected to solid-phase polymerization in a solid-phase polymerization reactor or a rotatable vacuum dryer at 140-200°C for approximately 10-24 hours under high vacuum inert airflow conditions.

[0081] As an example, the solid-phase polymerization can be carried out until the melt flow index (MFI) of the solid-phase polymer, measured at 230°C and a load of 2.16 kg in accordance with ASTM D-1238, is 30 g / 10 min or less, preferably 0.1 to 30 g / 10 min (230°C, 2.16 kg), and more preferably 1 to 30 g / 10 min (300°C, 1.2 kg), thereby producing a high-viscosity polymer.

[0082] The hardness of the polycarbonate (PC) can be expressed as Shore hardness D measured in accordance with ISO 868, and this hardness can be determined by the polyalkylene oxide content.

[0083] Polyalkylene oxide can be used in an amount of 10 to 50% by weight, preferably 15 to 50% by weight, and more preferably 15 to 45% by weight, relative to 100% by weight of the total polycarbonate (PC), such that the Shore hardness D of the polycarbonate (PC) is 35 to 60, preferably 40 to 55. Within this range, the polycarbonate (PC) has a low hardness, resulting in good flexibility, excellent heat resistance, and good compatibility of the resin.

[0084] The content of polycarbonate (PC) may be, for example, 24% by weight or less, specifically 4 to 24% by weight, preferably 5 to 22% by weight, based on 100% by weight of the total amount of all components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based copolycarbonate (Si-PC), glass fiber, and additives). If the content exceeds the above range, there is a disadvantage that the heat distortion temperature of the molded article manufactured using the thermoplastic resin composition containing it decreases, and if it is below the above range, there is a disadvantage that the laser transmittance of the molded article manufactured using the thermoplastic resin composition containing it decreases.

[0085] Siloxane-based copolycarbonate (Si-PC) A siloxane-based copolycarbonate (Si-PC) according to one embodiment of the present invention means a copolymer that simultaneously contains polycarbonate repeating units in which a polysiloxane structure is not introduced into the main chain and polycarbonate repeating units in which a polysiloxane structure is introduced into the main chain.

[0086] The aforementioned copolycarbonate simultaneously comprises a first repeating unit that does not have a siloxane bond, represented by the following chemical formula 1, and a second repeating unit that has one or more siloxane bonds, including repeating units represented by the following chemical formulas 2 and 3, respectively.

[0087] In this case, the molar ratio of the first aromatic polycarbonate repeating unit to the second aromatic polycarbonate repeating unit having one or more siloxane bonds is preferably 1:0.004 to 0.006, and the weight ratio is preferably 1:0.04 to 0.07.

[0088] Specifically, the repeating unit represented by chemical formula 1 below is formed by the reaction of an aromatic diol compound and a carbonate precursor.

[0089] [ka]

[0090] In the above chemical formula 1, preferably, R1 to R4 are each independently hydrogen, methyl, chloro, or bromo.

[0091] Preferably, Z is an unsubstituted or phenyl-substituted linear or branched C1-10 alkylene, more preferably methylene, ethane-1,1-diyl, propane-2,2-diyl, butane-2,2-diyl, 1-phenylethane-1,1-diyl, or diphenylmethylene.

[0092] Preferably, Z is cyclohexane-1,1-diyl, O, S, SO, SO2, or CO.

[0093] The repeating unit represented by the above chemical formula 1 is bis(4-hydroxyphenyl)methane, bis(4-hydroxyphenyl)ether, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)ketone, 1,1-bis(4-hydroxyphenyl)ethane, bisphenol A, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, 2,2-bis(4-hydroxy-3,5- It can be derived from one or more aromatic diol compounds selected from the group consisting of dichlorophenyl)propane, 2,2-bis(4-hydroxy-3-bromophenyl)propane, 2,2-bis(4-hydroxy-3-chlorophenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, bis(4-hydroxyphenyl)diphenylmethane, and α,ω-bis[3-(ο-hydroxyphenyl)propyl]polydimethylsiloxane.

[0094] The phrase "derived from an aromatic diol compound" means that the hydroxyl group of the aromatic diol compound reacts with a carbonate precursor to form a repeating unit represented by chemical formula 1. For example, when bisphenol A, an aromatic diol compound, and triphosgene, a carbonate precursor, are polymerized, the first repeating unit represented by chemical formula 1 is represented by the following chemical formula 1-1.

[0095] [ka]

[0096] As the carbonate precursor, one or more selected from the group consisting of dimethyl carbonate, diethyl carbonate, dibutyl carbonate, dicyclohexyl carbonate, diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, di-m-cresyl carbonate, dinaphthyl carbonate, bis(diphenyl) carbonate, phosgene, triphosgene, diphosgene, bromophosgene, and bishaloformate can be used. Preferably, triphosgene or phosgene can be used.

[0097] Specifically, the units represented by the chemical formula 2 below can be expressed as follows:

[0098] [ka]

[0099] In the above chemical formula 2, X1 is independently a C1-10 alkylene, R5 consists of four independently hydrogen atoms; unsubstituted or oxyranyl atoms; C1-10 alkoxy atoms substituted with oxyranyl atoms; C1-15 alkyl atoms substituted with C6-20 aryl atoms; halogen atoms; C1-10 alkoxy atoms; allyl atoms; C1-10 haloalkyl atoms; or C6-20 aryl atoms, and n is an integer from 1 to 200.

[0100] In the above chemical formula 2, preferably, X1 is independently a C2-10 alkylene, more preferably a C2-4 alkylene, and most preferably propane-1,3-diyl.

[0101] Preferably, R5 consists of four independent atoms: hydrogen, methyl, ethyl, propyl, 3-phenylpropyl, 2-phenylpropyl, 3-(oxyranylmethoxy)propyl, fluoro, chloro, bromo, iodine, methoxy, ethoxy, propoxy, allyl, 2,2,2-trifluoroethyl, 3,3,3-trifluoropropyl, phenyl, or naphthyl.

[0102] Preferably, R5 consists of four independently C1-10 alkyl groups, more preferably C1-6 alkyl groups, even more preferably C1-3 alkyl groups, and most preferably methyl groups.

[0103] Preferably, n is an integer between 10 and 50.

[0104] More preferably, n is an integer that is 10 or greater, 15 or greater, 20 or greater, 25 or greater, 30 or greater, 31 or greater, or 32 or greater, and is 50 or less, 45 or less, 40 or less, 39 or less, 38 or less, 37 or less, or 35 or less.

[0105] Furthermore, the repeating unit represented by chemical formula 3 can be shown as follows:

[0106] [ka]

[0107] In the above chemical formula 3, X2 consists of two independent C1-10 alkylenes, Y1 consists of two independent hydrogen, C1-6 alkyl, halogen, hydroxyl, C1-6 alkoxy, or C6-20 aryl atoms, R6 consists of four independent hydrogen atoms; C1-15 alkyl atoms that are unsubstituted or substituted with oxyranyl, oxyranyl-substituted C1-10 alkoxy, or C6-20 aryl atoms; halogen atoms; C1-10 alkoxy; allyl atoms; C1-10 haloalkyl atoms; or C6-20 aryl atoms, and m is an integer between 1 and 200.

[0108] Furthermore, in the above chemical formula 3, preferably, X2 consists of two independent C2-10 alkylenes, more preferably C2-6 alkylenes, and most preferably isobutylene.

[0109] Preferably, Y1 is hydrogen.

[0110] Preferably, R6 consists of four independent atoms: hydrogen, methyl, ethyl, propyl, 3-phenylpropyl, 2-phenylpropyl, 3-(oxyranylmethoxy)propyl, fluoro, chloro, bromo, iodine, methoxy, ethoxy, propoxy, allyl, 2,2,2-trifluoroethyl, 3,3,3-trifluoropropyl, phenyl, or naphthyl.

[0111] Furthermore, preferably, R6 consists of four independently C1-10 alkyl groups, more preferably C1-6 alkyl groups, even more preferably C1-3 alkyl groups, and most preferably methyl groups.

[0112] Preferably, m is an integer between 40 and 100. More preferably, m is an integer between 40 and 45, 50 and 55, 56 and 57, or 58 and 100 or less, 80 or less, 75 or less, 70 or less, 65 or less, 64 or less, 63 or less, or 62 or less.

[0113] The repeating unit represented by chemical formula 2 and the repeating unit represented by chemical formula 3 are derived from the siloxane compound represented by chemical formula 2-1 and the siloxane compound represented by chemical formula 3-1, respectively.

[0114] [ka]

[0115] In the aforementioned chemical formula 2-1, the definitions of X1, R5, and n are as previously defined.

[0116] [ka]

[0117] In the aforementioned chemical formula 3-1, the definitions of X2, Y1, R6, and m are as previously defined.

[0118] The phrase "derived from a siloxane compound" means that the hydroxyl group of each siloxane compound reacts with the carbonate precursor to form the repeating units represented by chemical formula 2 and chemical formula 3, respectively.

[0119] The carbonate precursors that can be used to form the repeating units of chemical formulas 2 and 3 are as described above in relation to the carbonate precursors that can be used to form the repeating units of chemical formula 1.

[0120] A method for producing the siloxane compound represented by chemical formula 2-1 and the siloxane compound represented by chemical formula 3-1 is, as an example, as shown in reaction formula 1 and reaction formula 2 below, respectively.

[0121] [ka]

[0122] In the above reaction equation 1, X1' is a C2-10 alkenyl, and the definitions of X1, R5, and n are as previously defined.

[0123] [ka]

[0124] In the above reaction equation 2, X2' is a C2-10 alkenyl, and the definitions of X2, Y1, R6, and m are as previously defined.

[0125] The reactions of reaction formulas 1 and 2 are preferably carried out under metal catalyst conditions. A Pt catalyst is preferred as the metal catalyst, and one or more Pt catalysts selected from the group consisting of Ashby catalyst, Karstedt catalyst, Lamoreaux catalyst, Speier catalyst, PtCl2(COD), PtCl2(benzonitrile)2, and H2PtBr6 can be used.

[0126] The metal catalyst can be used in amounts of 0.001 parts by weight or more, 0.005 parts by weight or more, or 0.01 parts by weight or more, based on 100 parts by weight of the compound represented by chemical formula 7 of reaction formula 1 or chemical formula 9 of reaction formula 2, and can be used in amounts of 1 part by weight or less, 0.1 parts by weight or less, or 0.05 parts by weight or less.

[0127] The reaction temperature is preferably 80 to 100°C.

[0128] The reaction time is preferably 1 to 5 hours.

[0129] The compound represented by chemical formula 7 or chemical formula 9 can be produced by reacting an organodisiloxane and an organocyclosiloxane under an acid catalyst, and the n and m can be adjusted by adjusting the content of the reactants. The reaction temperature is preferably 50 to 70°C. The reaction time is preferably 1 to 6 hours.

[0130] As the organodisiloxane, one or more selected from the group consisting of tetramethyldisiloxane, tetraphenyldisiloxane, hexamethyldisiloxane, and hexaphenyldisiloxane can be used.

[0131] Furthermore, the organocyclosiloxane can be, for example, an organocyclotetrasiloxane, such as octamethylcyclotetrasiloxane and octaphenylcyclotetrasiloxane.

[0132] The organodisiloxane can be used in an amount of 0.1 parts by weight or more, or 2 parts by weight or more, based on 100 parts by weight of the organocyclosiloxane, and in an amount of 10 parts by weight or less, or 8 parts by weight or less.

[0133] As the acid catalyst, one or more selected from the group consisting of H2SO4, HClO4, AlCl3, SbCl5, SnCl4, and acid clay can be used.

[0134] Furthermore, the acid catalyst can be used in amounts of 0.1 parts by weight or more, 0.5 parts by weight or more, or 1 part by weight or more, based on 100 parts by weight of organocyclosiloxane, and in amounts of 10 parts by weight or less, 5 parts by weight or less, or 3 parts by weight or less.

[0135] In particular, by adjusting the content of the repeating units represented by chemical formula 2 and the repeating units represented by chemical formula 3, the low-temperature impact strength and YI (Yellow Index) of siloxane-based copolycarbonate (Si-PC) can be improved simultaneously.

[0136] The weight ratio between the repeating units may be 1:99 to 99:1. Preferably, it is 3:97 to 97:3, 5:95 to 95:5, 10:90 to 90:10, or 15:85 to 85:15, and more preferably 20:80 to 80:20. The weight ratio of the repeating units corresponds to the weight ratio of the siloxane compounds, for example, the siloxane compound represented by chemical formula 2-1 and the siloxane compound represented by chemical formula 3-1.

[0137] Preferably, the repeating unit represented by chemical formula 2 is represented by the following chemical formula 2-2:

[0138] [ka]

[0139] In the aforementioned chemical formula 2-2, R5 and n are as defined above.

[0140] Preferably, R5 is methyl.

[0141] Furthermore, preferably, the repeating unit represented by chemical formula 3 is represented by the following chemical formula 3-2:

[0142] [ka]

[0143] In the aforementioned chemical formula 3-2, R6 and m are as defined above.

[0144] Preferably, R6 is methyl.

[0145] Preferably, the weight ratio of the repeating unit represented by chemical formula 1 to the total weight of the repeating unit represented by chemical formula 2 and the repeating unit represented by chemical formula 3 (chemical formula 1:(chemical formula 2+chemical formula 3)) is 1:0.001 to 1:0.2, and more preferably 1:0.01 to 1:0.1. The weight ratio of the repeating units corresponds to the weight ratio of the aromatic diol compound used to form the repeating unit of chemical formula 1 to the siloxane compound used to form the repeating units of chemical formulas 2 and 3.

[0146] The siloxane-based copolycarbonate (Si-PC) has a weight-average molecular weight of 1,000 to 100,000 g / mol, more preferably 15,000 to 35,000 g / mol. More preferably, the weight-average molecular weight (g / mol) is 23,000 or more, 24,000 or more, or 25,000 or more. Alternatively, the weight-average molecular weight may be 34,000 or less, 33,000 or less, or 32,000 or less.

[0147] The siloxane-based copolycarbonate (Si-PC) may, for example, be produced by polymerizing the aromatic diol compound, the siloxane compound represented by chemical formulas 2-1 and 3-1, and a carbonate precursor.

[0148] During polymerization, the siloxane compound is present in an amount of 0.1% by weight or more, or 3.0% by weight or more, relative to 100% by weight of the total of the aromatic diol compound, carbonate precursor, and one or more siloxane compounds. It can also be used in amounts of 0.5% by weight or more, 1% by weight or more, 1.5% by weight or more, 2.0% by weight or more, 2.5% by weight or more, 20% by weight or less, 10% by weight or less, 7% by weight or less, 5% by weight or less, or 4% by weight or less.

[0149] The aromatic diol compound can be used in an amount of 40% or more, 50% or more, or 55% or more by weight, relative to 100% by weight of the total of the aromatic diol compound, carbonate precursor, and one or more siloxane compounds, and can be used in an amount of 80% or less, 70% or less, or 65% or less by weight.

[0150] The carbonate precursor is present in an amount of 10% or more, 20% or more, or 30% by weight relative to 100% by weight of the total of the aromatic diol compound, the carbonate precursor, and one or more siloxane compounds, and can be used at an amount of 60% or less by weight, 50% or less by weight, or 40% or less by weight.

[0151] As an example of the polymerization method, an interfacial polymerization method can be used. In this case, the polymerization reaction can be carried out at atmospheric pressure and low temperature, and the molecular weight can be easily adjusted.

[0152] The aforementioned interfacial polymerization is preferably carried out in the presence of an acid binder and an organic solvent.

[0153] Furthermore, the interfacial polymerization may, for example, include a step of adding a coupling agent after prepolymerization and then polymerizing again, in which case a high molecular weight copolymer can be obtained.

[0154] The substance used in the aforementioned interfacial polymerization is not particularly limited as long as it is a substance that can be used for the polymerization of polycarbonate, and the amount used can be adjusted as needed.

[0155] As examples of the acid binder, alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, or amine compounds such as pyridine can be used.

[0156] The aforementioned organic solvent is not particularly limited as long as it is a solvent commonly used in the polymerization of polycarbonates. For example, halogenated hydrocarbons such as methylene chloride and chlorobenzene can be used.

[0157] The aforementioned interfacial polymerization may be further accelerated by the use of reaction accelerators such as tertiary amine compounds, quaternary ammonium compounds, and quaternary phosphonium compounds, including triethylamine, tetra-n-butylammonium bromide, and tetra-n-butylphosphonium bromide.

[0158] The reaction temperature for the interfacial polymerization is preferably 0 to 40°C, and the reaction time is preferably 10 minutes to 5 hours.

[0159] Furthermore, it is preferable to maintain the pH at 9 or higher, or 11 or higher, during the interfacial polymerization reaction.

[0160] Furthermore, the interfacial polymerization can be carried out with a molecular weight modifier. The molecular weight modifier can be added before, during, or after the start of polymerization.

[0161] A monoalkylphenol can be used as the molecular weight modifier. The monoalkylphenol is, for example, one or more selected from the group consisting of p-tert-butylphenol, p-cumylphenol, decylphenol, dodecylphenol, tetradecylphenol, hexadecylphenol, octadecylphenol, eicosylphenol, docosylphenol, and triacontylphenol. Preferably, it is p-tert-butylphenol, in which case the molecular weight modifier effect is greater.

[0162] The molecular weight adjusting agent is, for example, 0.01 parts by weight or more, 0.1 parts by weight or more, or 1 part by weight or more, based on 100 parts by weight of the aromatic diol compound, and is included in amounts of 10 parts by weight or less, 6 parts by weight or less, or 5 parts by weight or less, and within this range, the desired molecular weight can be obtained.

[0163] Siloxane-based copolycarbonates (Si-PCs) may be manufactured and used by methods known in the art, or commercially available substances may be used, without particular limitation.

[0164] The siloxane-based copolycarbonate (Si-PC) can be included in the thermoplastic resin composition in an amount of 22% by weight or less, specifically 10-21% by weight, and preferably 13-21% by weight, based on 100% by weight of the total amount of all components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based copolycarbonate (Si-PC), glass fiber, and additives). In this case, a balance of physical properties between the heat distortion temperature and impact strength can be achieved.

[0165] glass fiber In the present invention, the glass fibers may be unsized glass fibers or sized glass fibers with an adhesive. The adhesive is selected from the group consisting of silane coupling agents, urethane adhesives, epoxide adhesives, and / or amino-silane copolymers.

[0166] In the present invention, preferred silane coupling agents are at least one selected from the group consisting of epoxy-functional silanes, urethane-functional silanes, and aminoureido-functional silanes, more preferably at least one selected from the group consisting of epoxycyclohexyl-functional silanes, glycidoxy-functional silanes, isocyanate-functional silanes, and aminoureido-functional silanes, most preferably 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, At least one selected from N-2-(aminoethyl)-3-aminopropyltributoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropyldimethylmethoxysilane, 3-aminopropyldimethylethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, 3-ureidopropyltrialkoxysilane, and 3-isocyanatetopropyltriethoxysilane.

[0167] Preferred polyurethane adhesives are polyurethane adhesives such as one-component polyurethane adhesives or two-component polyurethane adhesives.

[0168] In the present invention, the glass fibers are preferably chopped or milled glass fibers. The glass fibers can have various cross-sections, such as circular or non-circular.

[0169] The average length of the glass fibers is preferably in the range of 3 to 9 mm or 3 to 6 mm, and the average diameter of the cross-section of the glass fibers is preferably in the range of 7 to 15 μm or 7 to 14 μm. Within this range, the reinforcing effect is maximized without adversely affecting the heat distortion temperature.

[0170] The average length and average diameter mentioned above may be the average values ​​of 10 measurements taken using a conventional method.

[0171] Glass fibers may be manufactured and used by methods known in the art, or commercially available materials may be used, but are not particularly limited.

[0172] The glass fibers can be included in the thermoplastic resin composition in an amount of 10 to 40% by weight, specifically 15 to 30% by weight, and preferably 25 to 33% by weight, based on 100% by weight of the total amount of all components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based copolycarbonate (Si-PC), glass fibers, and additives). In this case, a balance of physical properties between the heat distortion temperature and impact strength can be achieved.

[0173] For example, E-glass fiber can be used.

[0174] As a specific example, NEG T187H grade glass from Nippon Electric Glass Co., Ltd. can be used.

[0175] thermoplastic resin composition A thermoplastic resin composition according to one embodiment of the present invention may contain appropriate additives to improve its flowability and other properties.

[0176] As an example, the additive may be present in an amount of 0.01 to 10% by weight, preferably 0.1 to 8% by weight, more preferably 0.1 to 5% by weight, still preferably 0.1 to 5% by weight, and most preferably 0.1 to 1% by weight, based on 100% by weight of the total amount of all components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based polycarbonate copolymer (Si-PC), glass fiber, and additive). If the amount is less than the range described above, molded articles manufactured using the thermoplastic resin composition containing it will have the disadvantage of reduced physical properties and discoloration due to severance of the polymer molecular chains. If the amount is greater than the range described above, molded articles manufactured using the thermoplastic resin composition containing it will have the disadvantage of reduced rigidity and heat resistance.

[0177] The aforementioned additive may include, as an example, one or more selected from nucleating agents, lubricants, talc, antioxidants, and colorants.

[0178] The nucleating agent can be of known type, as long as it does not adversely affect the thermoplastic resin composition of the present invention. Among commercially available substances, sodium ionomer series compounds can be used as an example.

[0179] The nucleating agent may, for example, be included in an amount of 0.01 to 5% by weight, preferably 0.1 to 3% by weight, more preferably 0.1 to 2% by weight, still preferably 0.1 to 1% by weight, and most preferably 0.1 to 0.5% by weight, based on 100% by weight of the total amount of all components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based polycarbonate copolymer (Si-PC), glass fiber, and additives). If the content of the nucleating agent is too high outside the above range, there is a disadvantage that the laser transmittance of molded articles manufactured using the thermoplastic resin composition containing it will be low.

[0180] The lubricant is not particularly limited as long as it ensures ease of removal and flowability of the injection screw used to manufacture molded articles from a thermoplastic resin composition containing it, but preferably it may include polyethylene-based wax.

[0181] As an example, the lubricant may be 0.01 to 5% by weight, preferably 0.1 to 3% by weight, more preferably 0.1 to 2% by weight, still preferably 0.1 to 1% by weight, and most preferably 0.1 to 0.5% by weight, based on 100% by weight of the total components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), glass fiber, and additives). If the lubricant content is too high outside the above range, surface irregularities and other appearance problems may occur on molded articles manufactured using the thermoplastic resin composition containing it, which is detrimental to appearance quality.

[0182] The lubricant can be of any known type, as long as it does not adversely affect the thermoplastic resin composition of the present invention.

[0183] The talc is preferably a product that is an inorganic particle in the form of a plate, is chemically a mineral belonging to the hydrated magnesium silicate salt, and is generally used as a strength reinforcing agent for thermoplastic materials.

[0184] The talc may have an average particle size of 4.0 ± 0.5 μm or 4.0 ± 0.3 μm, and within this range, it is possible to sufficiently reinforce the strength without adversely affecting the heat distortion temperature of the thermoplastic resin.

[0185] The amount of talc added may, for example, be 0.01 to 5% by weight, preferably 0.1 to 3% by weight, more preferably 0.1 to 2% by weight, still preferably 0.1 to 1% by weight, and most preferably 0.1 to 0.5% by weight, based on 100% by weight of the total components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), glass fiber, and additives). If the talc content is too high outside the above range, the laser transmittance of molded articles manufactured using the thermoplastic resin composition containing it will decrease, and if the amount used is too small, the improvement in strength may be insufficient.

[0186] The talc can be of any known type, as long as it does not adversely affect the thermoplastic resin composition of the present invention.

[0187] The antioxidant is not particularly limited as long as it can prevent high-temperature deformation of molded articles manufactured using a thermoplastic resin composition containing it. For example, it may contain a primary antioxidant, a secondary antioxidant, or both. In this case, it has the effect of preventing oxidation due to heat during the extrusion process and providing excellent mechanical properties.

[0188] The primary antioxidant and secondary antioxidant may be included in a weight ratio of 1:0.5 to 1.5 (primary antioxidant:secondary antioxidant), 1:0.5 to 1.2, or 1:0.5 to 1, respectively. In this case, there is an effect of providing a balance of processability and physical properties.

[0189] The primary antioxidant may preferably be a phenolic antioxidant, and as an example, it may include a hindered phenolic stabilizer having a crystallization temperature (Tm) of 110 to 130°C. Specific examples include tetrakis[ethylene-3-(3,5-di-t-butyl-hydroxyphenyl)propionate], octadecyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, or a combination thereof.

[0190] In this description, the crystallization temperature (Tm) refers to the temperature at which crystallization occurs, in which the irregular structure of a substance changes to a regular arrangement due to the attractive forces between molecules and atoms. This temperature can be measured using a differential scanning calorimetry (DSC). As a specific example of measuring the crystallization temperature, approximately 0.5 mg to 10 mg of the sample is filled into a measuring container, the nitrogen gas flow rate is set to 20 ml / min, and to ensure the same thermal history for all samples, the temperature is raised from 0°C to 150°C at a rate of 20°C, maintained at this temperature for 2 minutes, and then cooled again from 150°C to -100°C at a rate of 10°C. The peak of the cooling curve of the heat flow measured by the DSC, i.e., the exothermic peak temperature during cooling, can be measured as the crystallization temperature. In this case, "peak" refers to the vertex of the cooling curve or the heating curve described later. For example, inflection points where the sign of the tangent slope changes, with the point where the tangent slope is 0 as the reference, are excluded.

[0191] As an example, the primary antioxidant may be 0.01 to 5% by weight, preferably 0.01 to 3% by weight, more preferably 0.01 to 2% by weight, still preferably 0.01 to 1% by weight, and most preferably 0.05 to 0.5% by weight, based on 100% by weight of the total components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), glass fiber, and additives). If the content of the primary antioxidant is too high, surface irregularities and other appearance problems may occur on molded articles manufactured using the thermoplastic resin composition containing it, which has the disadvantage of impairing appearance quality.

[0192] The secondary antioxidant may preferably be a phosphorus-based antioxidant, and as an example, it may include a phosphite-based antioxidant, specifically tris-(2,4-di-tert-butylphenyl) phosphite, di-(2,4-di-t-butylphenyl)pentaerythritol diphosphite, or a mixture thereof.

[0193] As an example, the secondary antioxidant may be 0.01 to 5% by weight, preferably 0.01 to 3% by weight, more preferably 0.01 to 2% by weight, still preferably 0.01 to 1% by weight, and most preferably 0.1 to 0.5% by weight, based on 100% by weight of the total components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), glass fiber, and additives). If the content of the secondary antioxidant is too high, surface irregularities and other appearance problems may occur on molded articles manufactured using the thermoplastic resin composition containing it, which has the disadvantage of impairing appearance quality.

[0194] As the primary and secondary antioxidants, a wide variety of known types can be used, as long as they do not adversely affect the thermoplastic resin composition of the present invention.

[0195] The colorant according to the present invention may be a coloring agent including a dye or a pigment.

[0196] The aforementioned dye may be a blue-violet dye or a red-orange dye, etc.

[0197] The aforementioned blue-violet dye may be anthraquinone.

[0198] The aforementioned red-orange dye may be perinone.

[0199] The aforementioned pigment may, for example, be an inorganic pigment.

[0200] The inorganic pigment may, for example, be one or more selected from the group consisting of metal compounds such as Ti, Pb, Fe, and Cr, and the metal compound may preferably be a metal oxide or a metal hydroxide.

[0201] The colorant may, for example, be present in an amount of 0.01 to 5% by weight, preferably 0.01 to 3% by weight, more preferably 0.1 to 3% by weight, and even more preferably 0.2 to 3% by weight, based on 100% by weight of the total amount of all components constituting the thermoplastic resin composition (polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based polycarbonate copolymer (Si-PC), glass fiber, and additives). If the content of the colorant is too high, it has the disadvantage of impairing the crack resistance quality of molded articles manufactured using the thermoplastic resin composition containing it.

[0202] A thermoplastic resin composition according to one embodiment of the present invention is characterized by containing polybutylene terephthalate (PBT) and polycarbonate homopolymer (PC) in a weight ratio of 1:0.3 to 1:1.1 (PBT:PC) or 1:0.4 to 1:1.0 (PBT:PC). In this case, the heat distortion temperature and impact strength are improved, the balance of physical properties is satisfied, and appropriate product reliability for electrical components can be provided.

[0203] A thermoplastic resin composition according to one embodiment of the present invention is characterized in that the weight ratio of polybutylene terephthalate (PBT) to polycarbonate homopolymer (PC) and siloxane-based polycarbonate copolymer (Si-PC) is within the range of 4:6 to 6:4 (PBT:PC + Si-PC) or 4.5:5.5 to 5.5:4.5 (PBT:PC + Si-PC). In this case, the heat distortion temperature and impact strength are improved, the balance of physical properties is satisfied, and appropriate product reliability for electrical components can be provided.

[0204] A thermoplastic resin composition according to one embodiment of the present invention is characterized in that the content ratio of polycarbonate homopolymer (PC) to siloxane-based polycarbonate copolymer (Si-PC) is within the range of 3.5:6.5 to 6.5:3.5 by weight (PC:Si-PC), or 3.8:6.2 to 6.2:3.8 by weight (PC:Si-PC). In this case, the heat distortion temperature and impact strength are improved, the balance of physical properties is satisfied, and appropriate product reliability for electrical components can be provided.

[0205] A thermoplastic resin composition according to one embodiment of the present invention is characterized in that, when the amount of polybutylene terephthalate (PBT) used is a, the amount of glass fiber used is b, and the amount of polycarbonate homopolymer (PC) used is c, a > b > c is satisfied. In this case, the heat distortion temperature and impact strength are improved, the balance of physical properties is satisfied, and appropriate product reliability for electrical components can be provided.

[0206] A thermoplastic resin composition according to one embodiment of the present invention is characterized in that, when the amount of polybutylene terephthalate (PBT) used is a', the amount of glass fiber used is b', and the amount of siloxane-based polycarbonate copolymer (Si-PC) used is d, the condition a'>b'>d is satisfied. In this case, the heat distortion temperature and impact strength are improved, the balance of physical properties is satisfied, and appropriate product reliability for electrical components can be provided.

[0207] A thermoplastic resin composition according to one embodiment of the present invention is characterized in that, in a total of 100% by weight of a base resin consisting of polybutylene terephthalate (PBT), polycarbonate homopolymer (PC), and siloxane-based polycarbonate copolymer (Si-PC); glass fibers; and additives, the composition contains 34.58 to 37% by weight of polybutylene terephthalate (PBT), 24% or less by weight of polycarbonate homopolymer (PC), 24% or less by weight of siloxane-based polycarbonate copolymer (Si-PC), and 10 to 40% by weight of glass fibers. In this case, the heat distortion temperature and impact strength can be improved, the balance of physical properties can be satisfied, and appropriate product reliability for electrical components can be provided.

[0208] The thermoplastic resin composition may be used in injection molded articles.

[0209] The thermoplastic resin composition may be used in electrical components.

[0210] The aforementioned electrical components may include connectors, sensor components, or components for a parking brake system.

[0211] The aforementioned sensor component may be a radome, an advanced driver-assistance system (ADAS), or the like.

[0212] Method for manufacturing thermoplastic resin compositions The following describes a method for producing the thermoplastic resin composition of the present invention. The description of the method for producing the thermoplastic resin composition of the present invention includes all the details of the thermoplastic resin composition described above.

[0213] The method for producing the thermoplastic resin composition described herein may include, as an example, the steps of putting a base resin consisting of polybutylene terephthalate (PBT), polycarbonate homopolymer (PC), and siloxane-based polycarbonate copolymer (Si-PC); glass fibers; and additives into an extruder, melt-mixing, and extruding.

[0214] The content ratio of polybutylene terephthalate (PBT) to polycarbonate homopolymer (PC) and siloxane-based polycarbonate copolymer (Si-PC) may be within the range of a weight ratio of 4:6 to 6:4 (PBT:PC + Si-PC).

[0215] The content ratio of the polycarbonate homopolymer (PC) to the siloxane-based polycarbonate copolymer (Si-PC) can satisfy a weight ratio of 3.5:6.5 to 6.5:3.5 (PC:Si-PC).

[0216] When the amount of polybutylene terephthalate (PBT) used is a, the amount of glass fiber used is b, and the amount of polycarbonate homopolymer (PC) used is c, the condition a > b > c can be satisfied.

[0217] When the amount of polybutylene terephthalate (PBT) used is a', the amount of glass fiber used is b', and the amount of siloxane-based polycarbonate copolymer (Si-PC) used is d, the condition a'>b'>d can be satisfied.

[0218] The base resin consisting of polybutylene terephthalate (PBT), polycarbonate homopolymer (PC), and siloxane-based polycarbonate copolymer (Si-PC); glass fibers; and additives; can be made up of a total of 100% by weight of the following: polybutylene terephthalate (PBT) in an amount of 34.58 to 37% by weight, polycarbonate homopolymer (PC) in an amount of 24% by weight or less, siloxane-based polycarbonate copolymer (Si-PC) in an amount of 24% by weight or less, and glass fibers in an amount of 25 to 33% by weight.

[0219] The melt-mixing step may, as an example, include the other additives mentioned above.

[0220] The melt-mixing and extrusion steps may, for example, be carried out using one or more selected from the group consisting of a single-screw extruder, a twin-screw extruder, and a Banbury mixer, preferably a twin-screw extruder. After uniformly mixing the composition using this method, it can be extruded to obtain, for example, a pelletized thermoplastic resin composition. In this case, a decrease in mechanical properties and thermal properties is prevented, and there is an effect of excellent plating adhesion and appearance quality.

[0221] The step of producing pellets using the extruder can, for example, be carried out at an extrusion temperature of 230-300°C, a feed rate (flow ratio, F / R) of 50-90 kg / hr, and a screw rotation speed of 200-490 rpm, preferably at an extrusion temperature of 230-260°C, an F / R of 50-90 kg / hr, and a screw rotation speed of 250-350 rpm.

[0222] The procedure may include extruding the thermoplastic resin composition and then injecting it at an injection temperature of 240-280°C, specifically 250-270°C, a mold temperature of 40-80°C, specifically 50-70°C, and an injection speed of 10-80 mm / sec, specifically 20-60 mm / sec.

[0223] Figure 2 below shows a cross-section of an extruder used in a method for manufacturing a molded product according to one embodiment of the present invention.

[0224] The extruder may have, for example, six or more kneading blocks, preferably seven or more, more preferably eight or more, a preferred example being eight to fifteen, and a more preferred example being nine to twelve. In this case, it may be effective to use the kneading blocks in a combination in the forward direction, perpendicular direction, and reverse direction relative to the resin flow direction, and a combination of continuous or separated blocks may be used depending on the mixing method. In this case, the dispersibility of the components and the compatibility of the composition are further improved, and a higher quality kneaded product can be provided.

[0225] The type of extruder is not particularly limited, but considering uniform mixing and dispersion, ease of processing, and economic efficiency, it is preferable to use a twin-screw extruder with two screws.

[0226] The extruder comprises a feeder for supplying material into a barrel, a screw for transporting and kneading the material supplied into the barrel, and a die for extruding the kneaded material. The screw is composed of multiple screw elements to provide various functions.

[0227] The raw material feeder may consist of one or more, and may be selectively provided with two or more as needed. For example, it may be provided with a main inlet and optionally an auxiliary inlet, and may have two or more auxiliary inlets as needed.

[0228] For example, the entire component excluding the glass fibers can be introduced into the main inlet, and the halogenated glass fibers can be introduced into the auxiliary inlet 1.

[0229] As a specific example, referring to Figure 1 below, the extruder 100 may include first to third inlets 11, 12, 13 and first to third kneading blocks 21, 22, 23, and a substance fed in along the first direction (DR1) may be kneaded and discharged.

[0230] Specifically, the material injected into the first inlet 11 is kneaded as it moves to the first kneading block 21, and the first kneaded product may be formed in the first kneading block 21. The material injected into the second inlet 12 is mixed with the first kneaded product and kneaded as it moves to the second kneading block 22, and the second kneaded product may be formed in the second kneading block 22. In addition, the material injected into the third inlet 13 is mixed with the second kneaded product and kneaded as it moves to the third kneading block 23, and the final product may be formed in the third kneading block 23.

[0231] Furthermore, a molded article containing the thermoplastic resin composition of the present invention will be described. In describing a molded article containing the thermoplastic resin composition of the present invention, all of the contents of the thermoplastic resin composition described above will be included.

[0232] Molded product The thermoplastic resin composition of the present invention can be usefully applied to molded articles requiring high heat distortion temperature and impact strength through the synergy between its components.

[0233] The aforementioned molded articles can be manufactured by methods commonly used in this industry. For example, using a molten paste, pellets, or sheet (plate material) formed therefrom of the thermoplastic resin composition according to the present invention as a raw material, molding methods such as extrusion molding, casting, press molding, pressure molding, hot bending, compression molding, calendering, rotational molding, or injection molding and injection compression molding can be applied.

[0234] As an example, the thermoplastic resin composition described herein can be produced by using a twin-screw extruder (φ40, L / D:42, equipped with SM Platek) set to 230°C, feeding polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based copolycarbonate (Si-PC), glass fiber, and additives into the main inlet at a supply rate of 50 kg / h, melt-kneading, and extruding to produce pellets.

[0235] As an example, the thermoplastic resin composition described herein can be manufactured by using a twin-screw extruder (φ40, L / D:42, equipped with SM Platek) set to 260°C, feeding polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based copolycarbonate (Si-PC), and additives into the main inlet at 375 rpm, feeding glass fibers into the auxiliary inlet at a supply rate of 75 kg / h, and then melt-kneading and extruding to produce pellets.

[0236] The aforementioned pellets can be fed into an injection molding machine to manufacture molded products.

[0237] To indirectly confirm the physical properties of the manufactured molded product, the pellets can be injected using an injection molding machine (ENGEL, 80 tons) at an injection temperature of 260°C, a mold temperature of 60°C, and an injection speed of 30 mm / sec to produce test specimens conforming to ISO standards.

[0238] The manufactured test specimens may have a flow index (260°C, 2.16 kgf) measured in accordance with ISO 1133, which may be 5 g / 10 min or higher, and more specifically, 10 to 20 g / 10 min.

[0239] A molded article containing the thermoplastic resin composition of the present invention may have a laser transmittance (%) of 67.5% or higher, specifically 67.5% to 80%, preferably 67.5% to 75%, as measured using an EVlaser ETM-31 (980nm) device.

[0240] The aforementioned laser transmittance was calculated by manufacturing a 60mm (width) x 60mm (height) x 1.5mm (thickness) rectangular test piece by injection molding a resin molded product and a material, as shown in Figure 1 below. The test piece was irradiated with a laser using an ETM-31 (EV Laser Co.) at a laser irradiation wavelength of 980nm and an output of 10mW at the gate area (A) and a non-gate area (B), respectively, and the reflected intensity value was measured. The laser transmittance was then calculated using Equation 1 shown below.

[0241] Furthermore, at this time, the laser transmittance was measured five times for each part. In Tables 3 and 4 below, the laser transmittance of the gate area is the average value of the measured laser transmittance of the gate area, and the maximum transmittance is the average value of the measured laser transmittance of the positions excluding the gate area.

[0242] [Formula 1] Laser transmittance (%) = 100 × Po / Pi

[0243] In the above formula 1, Po is the laser output after passing through the test specimen, and Pi is the laser input before passing through the test specimen.

[0244] Here, the laser power before passing through the test specimen may be, for example, 10 mW.

[0245] A molded article containing the thermoplastic resin composition of the present invention may have a heat distortion temperature of 167.6°C or higher, or more specifically, 167.6 to 185.4°C, when measured under a load of 0.45 MPa (flatwise) on a 4 mm thick test piece in accordance with ISO 75.

[0246] A molded article containing the thermoplastic resin composition of the present invention exhibits a room-temperature Izod impact strength (23°C, Notched) measured in accordance with ISO 180, for example, 9.5 kJ / m². 2 The above are specific examples: 9.75~11.52 kJ / m³ 2 That's fine.

[0247] A molded article containing the thermoplastic resin composition of the present invention exhibits a low-temperature Izod impact strength (-30°C, Notched) measured in accordance with ISO 180, for example, 8.4 kJ / m². 2 The above is a specific example: 8.55~9.8 kJ / m³ 2 That's fine.

[0248] A molded article containing the thermoplastic resin composition of the present invention may mean a molded article manufactured with the thermoplastic resin composition or a molded article manufactured containing the thermoplastic resin composition.

[0249] The molded product may specifically be an electrical component, but is not limited to any particular type.

[0250] In other words, a thermoplastic resin composition according to one embodiment of the present invention is characterized by containing polybutylene terephthalate (PBT), polycarbonate (PC), and siloxane-based copolycarbonate (Si-PC) in a predetermined blending ratio. In this case, molded articles produced from the thermoplastic resin composition satisfy the balance of physical properties between heat distortion temperature and impact strength, further improving the heat resistance required with the improvement of radar performance and the impact strength required with the diversification of radome applications, and having the advantage of being usable in a wider variety of radomes and other electrical components.

[0251] In describing the thermoplastic resin composition, its manufacturing method, and molded article of the present invention, other conditions and equipment not explicitly mentioned can be appropriately selected within the range of practices commonly used in the industry and are not particularly limited. Furthermore, unless otherwise defined, % means weight percent.

[0252] The following describes in detail embodiments of the present invention so that those with ordinary skill in the art to which the present invention pertains can easily implement it. However, the present invention can be realized in a variety of different forms and is not limited to the embodiments described herein.

[0253] [Examples] Examples 1-3 and Comparative Examples 1-8 The raw materials used in the examples and comparative examples are as follows: (A) Polybutylene terephthalate (PBT): Intrinsic viscosity (IV) 0.83, Product name TH6082A (B) Polycarbonate B-1) Polycarbonate (PC): The melting index measured at 300°C under 1.2 kg in accordance with ASTM D1238 was 22 g / 10 min, and the mold shrinkage rate measured in accordance with ASTM D955 was 0.005~0.007 in / in. LG Chem Co., Ltd., Product name LUPOY PC1300 B-2) Siloxane-based copolycarbonate (Si-PC): LG Chem Co., Ltd., Product name LUPOY PC8000-05 (C) Glass fiber: NEG's T-187H, with an average length of 7-15 μm. (D) Additives D-1) Nucleating agent: Bruggemann's P250 (sodium ionomer series) D-2) Talc: Koch's KC-3000 (average particle size 4.0 ± 0.5 μm) D-3) Primary antioxidant: IR 1010 D-4) Secondary antioxidant: PEP 36

[0254] After mixing the raw materials for the thermoplastic resin compositions listed in Tables 1 and 2 below, a thermoplastic resin composition with a uniform degree of dispersion was manufactured in pellet form by extrusion. Then, test specimens were prepared by an injection molding process in which the pellets were heated, injected into a mold, and cooled.

[0255] Specifically, the components shown in Tables 1 and 2 below were mixed in a mixer, and then extruded at a feed rate of 50 kg / h into the main inlet at 250 rpm using a twin-screw extruder (φ40, L / D:42, equipped with SM Platek) set to 250°C to produce pellets of thermoplastic resin composition. At this time, glass fibers were fed into the auxiliary inlet, and the extruder used had 9 mixing blocks.

[0256] The aforementioned pellets were dried in a convection oven at 120°C for more than 4 hours, and then test specimens were prepared by injecting them using an injection molding machine (ENGEL, 80 tons) at an injection temperature of 250°C, a mold temperature of 60°C, and an injection speed of 30 mm / sec.

[0257] [Table 1] (The raw materials used in Table 1 above should be added in units of weight percentage to the total weight of all materials A through D-4 combined (100% weight).)

[0258] [Table 2] (The raw materials used in Table 2 above are each added in units of wt%, based on 100 wt% of the total sum of A-1 to D-4.)

[0259] Test Example 1: Evaluation of the physical properties of molded product test specimens The physical properties of the molded product test pieces produced in the above Examples 1 to 3 and Comparative Examples 1 to 8 were evaluated. The evaluation criteria are as follows. -Laser transmittance (%): As shown in Figure 1 below, the resin molded product and the material were injection-molded to produce a square test piece of 60 mm (width) × 60 mm (length) × 1.5 mm (thickness). Using ETM-31 (EV Laser Inc.), the gate part (A) and the non-gate position (B) were each irradiated with a laser at a laser irradiation wavelength of 980 nm and an output of 10 mW, then the returning intensity value was measured, and calculation was performed according to Equation 1 as shown below.

[0260] At this time, the laser transmittance was measured 5 times for each site. The laser transmittance of the gate part in Table 3 and Table 4 below is the average value of the measured laser transmittance values of the gate part, and the maximum transmittance is the average value of the measured laser transmittance values at positions excluding the gate part.

[0261] [Equation 1] Laser transmittance (%) = 100 × Po / Pi

[0262] In the above Equation 1, Po is the laser output that has passed through the test piece, and Pi is the laser output before passing through the test piece.

[0263] -Heat distortion temperature (HDT): Measured in accordance with ISO 75 on a 4 mm thick test piece under a load of 0.45 MPa (flatwise).

[0264] -Normal temperature impact strength (IZOD): Measured in accordance with ISO 180 on a 4 mm thick test piece (Notched, 23°C).

[0265] - Low-temperature impact strength (IZOD): Measured on a 4mm thick specimen in accordance with ISO 180 (Notched, -30℃).

[0266] The results measured using the aforementioned evaluation criteria are shown in Tables 3 and 4 below.

[0267] [Table 3]

[0268] [Table 4]

[0269] Referring to Tables 3 and 4 above, it can be confirmed that the thermoplastic resin compositions of Examples 1 to 3 according to the present invention, by containing polybutylene terephthalate (PBT), polycarbonate (PC), and siloxane-based copolycarbonate (Si-PC) in predetermined blending ratios, improve the balance of physical properties between heat distortion temperature and impact strength, satisfying the heat resistance required with improved radar performance and the impact strength required with the diversification of radome applications, thereby providing product reliability. On the other hand, Comparative Examples 1 to 5, which do not contain siloxane-based copolycarbonate (Si-PC), showed a decrease in laser transmittance, room-temperature impact strength, and low-temperature impact strength compared to Example 1, and were found to be unable to provide the heat resistance required with improved radar performance and the impact strength required with the diversification of radome applications.

[0270] On the other hand, Comparative Example 5, which did not contain siloxane-based copolycarbonate (Si-PC) but incorporated polybutylene terephthalate (PBT) and polycarbonate (PC) within an appropriate range and did not use a nucleating agent or talc, showed improved laser transmittance and room temperature / low temperature impact strength compared to Comparative Examples 1-4, but also showed a significant reduction in thermal distortion temperature.

[0271] Furthermore, even though Comparative Example 6 contained siloxane-based copolycarbonate (Si-PC), it did not contain polycarbonate (PC), and it was confirmed that the laser transmittance decreased compared to Example 1.

[0272] Furthermore, even though Comparative Example 7 contained siloxane-based copolycarbonate (Si-PC), it was found that a small amount was used outside the appropriate range, resulting in a reduced heat distortion temperature compared to Example 2.

[0273] Furthermore, even though Comparative Example 8 contained siloxane-based copolycarbonate (Si-PC), it was found that the amount used was excessive and outside the appropriate range, resulting in decreased laser transmittance and thermal distortion temperature compared to Example 1.

[0274] In other words, the thermoplastic resin composition according to one embodiment of the present invention, by including polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based polycarbonate (Si-PC), and organic fibers, satisfies the balance of physical properties between the heat distortion temperature and impact strength of the manufactured molded product, satisfies the heat resistance required with the improvement of radar performance and the impact strength required with the diversification of radome applications, and is suitable for use in electrical components and the like. [Explanation of symbols]

[0275] 100 extruders 11 1st input port 12 2nd input port 13 3rd input port 21. First mixing block 22. Second Mixing Block 23. Third Mixing Block

Claims

1. It comprises polybutylene terephthalate (PBT), polycarbonate (PC), and siloxane-based copolycarbonate (Si-PC); and glass fiber; The weight ratio of polycarbonate (PC) and siloxane-based copolycarbonate (Si-PC) to polybutylene terephthalate (PBT) is in the range of 4:6 to 6:4 (PBT:PC + Si-PC). The weight ratio of the polycarbonate (PC) to the siloxane-based copolycarbonate (Si-PC) satisfies 3.5:6.5 to 6.5:3.5 (PC:Si-PC). When the amount of polybutylene terephthalate (PBT) used is a, the amount of glass fiber used is b, and the amount of polycarbonate (PC) used is c, then a > b > c is satisfied. A thermoplastic resin composition characterized in that, when the amount of polybutylene terephthalate (PBT) used is a', the amount of glass fiber used is b', and the amount of siloxane-based copolycarbonate (Si-PC) used is d, a' > b' > d.

2. Polybutylene terephthalate (PBT), polycarbonate (PC), and siloxane-based copolycarbonate (Si-PC); glass fiber; and additives; in a total of 100% by weight, The aforementioned polybutylene terephthalate (PBT) is contained in an amount of 31.3 to 37% by weight. The aforementioned polycarbonate (PC) is contained in an amount of 24% by weight or less. The aforementioned siloxane-based copolycarbonate (Si-PC) is contained in an amount of 24% by weight or less. A thermoplastic resin composition characterized by containing the aforementioned glass fibers in an amount of 10 to 40% by weight.

3. The thermoplastic resin composition according to claim 1 or 2, characterized in that the polybutylene terephthalate (PBT) has a weight-average molecular weight of 10,000 to 80,000 g / mol.

4. The thermoplastic resin composition according to claim 1 or 2, characterized in that the polybutylene terephthalate (PBT) and polycarbonate (PC) are contained in a weight ratio of 1:0.3 to 1:1.1 (PBT:PC).

5. The thermoplastic resin composition according to claim 1, characterized in that the polycarbonate (PC) is contained in an amount of 13 to 21% by weight in the total of 100% by weight of polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based copolycarbonate (Si-PC), glass fiber, and additives.

6. The thermoplastic resin composition according to claim 1, characterized in that the siloxane-based copolycarbonate (Si-PC) is contained in an amount of 13 to 21% by weight in the total of 100% by weight of polybutylene terephthalate (PBT), polycarbonate (PC), siloxane-based copolycarbonate (Si-PC), glass fiber, and additives.

7. The thermoplastic resin composition according to claim 1, characterized in that the polycarbonate (PC) has a melt index of 0.1 to 30 g / 10 min measured at 300°C and 1.2 kg in accordance with ASTM D1238, and a mold shrinkage rate of 0.005 to 0.007 in / in measured in accordance with ASTM D955.

8. The thermoplastic resin composition according to claim 1, characterized in that the glass fibers are chopped strands having an average diameter of 7 to 15 μm and an average length of 3 to 9 mm.

9. The thermoplastic resin composition according to claim 1, characterized in that the additive comprises one or more selected from nucleating agents, lubricants, talc, antioxidants, and colorants.

10. The thermoplastic resin composition according to claim 1, characterized in that the thermoplastic resin composition is a material used for electrical components.

11. The thermoplastic resin composition has a heat distortion temperature of 167.6°C or higher, measured under a load of 0.45 MPa (flatwise) on a 4 mm thick test specimen, in accordance with ISO 75. In accordance with ISO 180, the Izod impact strength at room temperature (23°C, Notched) measured on a 4 mm thick test specimen was 9.5 kJ / m². 2 In accordance with ISO 180, the low-temperature Izod impact strength (-30°C, Notched) measured on a 4 mm thick test specimen was 8.4 kJ / m². 2 The thermoplastic resin composition according to claim 1, characterized in that it is as described above.

12. The process includes the steps of putting polybutylene terephthalate (PBT), polycarbonate (PC), and siloxane-based copolycarbonate (Si-PC); glass fibers; and additives into an extruder, melting, kneading, and extruding. The weight ratio of polycarbonate (PC) and siloxane-based copolycarbonate (Si-PC) to polybutylene terephthalate (PBT) is in the range of 4:6 to 6:4 (PBT:PC + Si-PC). The weight ratio of the polycarbonate (PC) to the siloxane-based copolycarbonate (Si-PC) satisfies 3.5:6.5 to 6.5:3.5 (PC:Si-PC). When the amount of polybutylene terephthalate (PBT) used is a, the amount of glass fiber used is b, and the amount of polycarbonate (PC) used is c, then a > b > c is satisfied. A method for producing a thermoplastic resin composition, characterized in that when the amount of polybutylene terephthalate (PBT) used is a', the amount of glass fiber used is b', and the amount of siloxane-based copolycarbonate (Si-PC) used is d, the condition a' > b' > d is met.

13. Polybutylene terephthalate (PBT), polycarbonate (PC), and siloxane-based copolycarbonate (Si-PC); glass fiber; and additives; in a total of 100% by weight, The aforementioned polybutylene terephthalate (PBT) is contained in an amount of 31.3 to 37% by weight. The aforementioned polycarbonate (PC) is contained in an amount of 24% by weight or less. The aforementioned siloxane-based copolycarbonate (Si-PC) is contained in an amount of 24% by weight or less. A method for producing a thermoplastic resin composition, characterized by comprising the steps of introducing the glass fibers in an amount of 10 to 40% by weight into an extruder, melting and kneading, and extruding.

14. A molded article characterized by comprising the thermoplastic resin composition described in any one of claims 1 to 11.

15. The molded product according to claim 14, characterized in that the molded product is an electrical component.

Citation Information

Patent Citations

  • High-gloss polycarbonate resin composition with excellent chemical resistance, mechanical properties and light resistance, and product comprising the same

    KR1020200066480A